SURVEY AND DOCUMENTATION OF ETHNOVETERINARY HEALTHCARE PRACTICES USED BY RURAL PEOPLE OF AKOLA DISTRICT OF MAHARASHTRA - Jambu, Sangeeta; Wath, Manjusha (International Journal of Research -GRANTHAALAYAH, 2018)
The people of rural areas still depend to a large extent upon plants and household remedies for treating their animals. The present study deals with the survey and documentation of ethno veterinary medicinal plants used by rural people from Akola district. The ethnoveterinary information included with local name, family, parts used, local uses and its mode of preparation for ethnoveterinary treatments. The common cattle diseases of the area reported are foot and mouth diseases, black quarter, fracture, Diarrhoea and Dysentery and dysentery, blood dysentery, intestinal worm, tympani, prolapsed uterus, retention of placenta, wound, maggotted wound, fever, snake bite, eye diseases, ectoparasite (tick), galactagogue etc. In this study we observed that old aged people have more knowledge and experience particularly in remote areas for curing veterinary ailments. Ethnoveterinary medicine can provide an opportunity for new drug development.